The Intimate Picture of Queen Victoria and her Household, 1840–1843. Extracts from the Diary of Dr Robert Ferguson, the Queen’s Accoucheur (Theatrum historiae, 2017)
It is a critical edition of extracts from a virtually unknown diary of Dr Robert Ferguson, a physician and accoucheur to Queen Victoria. Acquired only in 2009, the diary is housed in the archives of the Royal College of Physicians in London. Its highlights include the details of royal arrangements for the birth of the Princess Royal, record of Ferguson’s interview with the Queen regarding her mental health in 1841, and most intimate character sketches of the Queen, her husband, Prince Albert, their closest advisor Baron Christian Stockmar, or the Queen’s former governess and confidante, Baroness Louise Lehzen.
Keywords: Queen Victoria; Prince Albert; Louise Lehzen; Christian Stockmar; Robert Ferguson’s diary; Royal Household; royal physicians; royal accoucheurs